2022
DOI: 10.3389/fendo.2022.938358
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiome and metabolic activity in type 1 diabetes: An analysis based on the presence of GADA

Abstract: ObjectiveType 1 diabetes (T1D) progression is affected by circulating glutamic acid decarboxylase antibody (GADA) that persist for many years. This study aimed at investigating whether and how the gut microbiome and its correlated metabolites change in T1D with the presence of GADA.MethodsWe used a radiobinding assay to measure GADA titers and identify the 49 T1D patients with GADA+ and 52 T1D patients with GADA-. The fresh feces and serum were analyzed using 16S rRNA gene sequencing and GC/MS. Then gut microb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…In addition, the gut microbiome may influence T1D progression through the production of microbial metabolites. Indeed, it has been shown that the gut microbiome of children diagnosed with T1D contains fewer fermenters that produce butyrate, a short chain fatty acid (SCFA) with anti-inflammatory actions that also enhances the immune regulatory response [10][11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the gut microbiome may influence T1D progression through the production of microbial metabolites. Indeed, it has been shown that the gut microbiome of children diagnosed with T1D contains fewer fermenters that produce butyrate, a short chain fatty acid (SCFA) with anti-inflammatory actions that also enhances the immune regulatory response [10][11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%